2020
DOI: 10.3390/s20061545
|View full text |Cite
|
Sign up to set email alerts
|

Induced Gamma-Band Activity during Actual and Imaginary Movements: EEG Analysis

Abstract: The purpose of this paper is to record and analyze induced gamma-band activity (GBA) (30–60 Hz) in cerebral motor areas during imaginary movement and to compare it quantitatively with activity recorded in the same areas during actual movement using a simplified electroencephalogram (EEG). Brain activity (basal activity, imaginary motor task and actual motor task) is obtained from 12 healthy volunteer subjects using an EEG (Cz channel). GBA is analyzed using the mean power spectral density (PSD) value. Event-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Since distinct EEG rhythms might relate to different cognitive and affective states [49], it is actually reasonable that FC patterns were not equal across all rhythms. In addition, it is worth observing that, even though MI is predominantly linked to rhythms within the α range (i.e., the µ band), this task could also induce the observed alterations for the β and γ bands; the latter, especially, is commonly overlooked in MI-EEG studies (notwithstanding, recent works have increasingly argued for the involvement of this band in this type of task-e.g., [50]). Moreover, as mentioned, functional links were more consistently found across subjects prior to the AO+MI-VR intervention.…”
Section: Group Analysismentioning
confidence: 99%
“…Since distinct EEG rhythms might relate to different cognitive and affective states [49], it is actually reasonable that FC patterns were not equal across all rhythms. In addition, it is worth observing that, even though MI is predominantly linked to rhythms within the α range (i.e., the µ band), this task could also induce the observed alterations for the β and γ bands; the latter, especially, is commonly overlooked in MI-EEG studies (notwithstanding, recent works have increasingly argued for the involvement of this band in this type of task-e.g., [50]). Moreover, as mentioned, functional links were more consistently found across subjects prior to the AO+MI-VR intervention.…”
Section: Group Analysismentioning
confidence: 99%
“…The increased gamma band power is thought to indicate sensorimotor integration in the motor cortex, re ecting motor planning 35,36 . In addition, these increases in gamma band power in the M1 and SMA are observed not only during actual motor execution, but also during motor imagery 37 . Taking such ndings into consideration, the correlation between gamma band activity in the precentral gyrus and the level of fatigue sensation observed in our study may suggest enhanced adjustment of motor planning in the precentral brain regions caused by the induction of a fatigue sensation to properly suppress motor output and thus maintain homeostasis.…”
Section: Discussionmentioning
confidence: 84%
“…Although the above metrics demonstrate good performance in classification approaches, it should be noted that AM classification can be more challenging, due to the presence of motion that can alter EEG signals [16,20]. Additionally, it has been shown that motionrelated therapies can generate greater motivation in HMI users than those based on imagination [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…This could be a barrier between the user and the system, which could cause demotivation and low Human Machine Interaction (HMI) [10,11]. Therefore, several studies have found that tasks that are harder to manipulate are also more difficult to manipulate mentally, which highlights the influence of realworld motor experiences on mental imagery [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation